Modification and Validation of the Treatment Self Regulation Questionnaire to Assess Parental Motivation for HPV Vaccination of Adolescents - Denman, Deanna C. (Vaccine, 2016)
BACKGROUND: According to Self-Determination Theory, the extent to which the motivation underlying behavior is self-determined or controlled influences its sustainability. This is particularly relevant for behaviors that must be repeated, such as completion of the human papillomavirus (HPV) vaccine series. To date, no measures of motivation for HPV vaccination have been developed. METHODS: As part of a larger study, parents (N=223) whose adolescents receive care at safety-net clinics completed a telephone questionnaire about HPV and the vaccine. We modified the Treatment Self-Regulation Questionnaire to assess parents’ motivation for HPV vaccination in both Spanish and English. We used confirmatory factor analysis to test a three-factor measurement model. RESULTS: The three-factor model fit the data well (RMSEA=.04, CFI=.98, TLI=.96), and the scales’ reliabilities were adequate (autonomous: α=.87; introjected: α=.72; external: α=.72). The factor loading strength for one item was stronger for Spanish- than English-speaking participants (p<.05); all others were equivalent. The intercorrelations among the scales ranged from −.17 to .32, suggesting discriminant factors. The scales displayed the expected pattern of correlations with other psychosocial determinants of behavior. Vaccination intentions showed a strong correlation with autonomous motivation (r= .52), but no correlation with external motivation (r=.02), suggesting autonomous motivation may be particularly important in vaccine decision-making. CONCLUSION: Findings support the use of three subscales to measure motivation in HPV vaccination and suggest possible cultural differences in motivation.